ANATOMICAL AND PHYSICAL PROPERTIESOF BISBUL WOOD (Diospyros blancoi A.DC.) - Krisdianto Krisdianto; Abdurachman Abdurachman (Indonesian Journal of Forestry Research, 2005)
Ebony (Diospyros sp.)  is a heavy hardwood that is  popularly known as blackwood. Diospyros consists of over 300 species spread throughout tropics area and about 100 species occur in Indonesia. Bisbul wood (Diospyros btancoi A.DC.) is one species of  streaked ebony that is locally known as 'buah mentega'.  The anatomical and physical properties of  bisbul  were studied to collect information  for wood identification  and to support appropriate use of the timber. Anatomical properties were studied from microtome sectioned samples, which have been coloured by safranin and mounted by entellan, while fiber dimensions  were studied from macerated samples.  Physical properties  of  bisbul wood studied include moisture content, density and percentage of volumetric shrinkage. Moisture content and density were studied from 20 x 20 x 20 mm samples based on wet and oven dry condition. Volumetric shrinkage was measured from dimension changes in radial, tangential and longitudinal shrinkage of 20 x 20 x 40 mm samples. The samples were measured in wet and oven dry conditions. The main anatomical characteristics to identify bisbul wood were black wood with pinkish streaked, heavy and very hard,  very fine texture, even, lustrous surface and glossy, distinct growth ring, small size of vessels, apotracheal parenchyma forming reticulate pattern. The average moisture content was 59.86 ± 2.84%,  the density average was 0.74 ± 0.04 gr/cm3  and volumetric shrinkage was 10.41±0.70%.   The higher the stem, the more moisture  content and the lower the density will be. Sapwood density was lower and had more moisture  content than heartwood. The black pinkish heavy wood, bisbul was recommended to be used for carvings, sculpture, souvenir and luxuryinterior products.